The Impact of Corporate Social Responsibility Disclosure on Financial Performance with Financial Statement Comparability as A Mediating - Riris Widyaningrum; Adhelia Desi Prawestri (UIN Raden Mas Said Surakarta, 2026)
This study aims to analyze the effect of Corporate Social Responsibility on financial performance, mediated by financial statement comparability. This is a quantitative study. The subjects of this study are infrastructure sector companies listed on the Indonesia Stock Exchange from 2021 to 2024. The sampling technique used was purposive sampling with a sample size of 192 observations. This study employed multiple linear regression analysis and path analysis to examine the effects of the hypotheses, utilizing EViews software. The study’s findings suggest that CSR does not significantly impact financial performance or financial statement comparability. Additionally, financial statement comparability does not significantly influence financial performance, nor does it mediate the relationship between CSR and financial performance. A mediating relationship cannot be established as the three variables do not exhibit a significant relationship. However, when combined with the control variables, they can influence financial performance.